Eksplorasi Tafsir Ilmi - Hanna Salsabila; Farhan Muhammad; Eni Zulaiha; Muhamad Yoga Firdaus (LPPM Institut Nasional Laa Roiba Bogor, 2023)
The purpose of this study is to explore Scientific Interpretation as a style of interpretation that uses a scientific approach in understanding the verses of the Qur'an. The method used in this research is qualitative through literature study using historical and scientific approaches. The results and discussion of this research include, the history of the development of scientific interpretation, limitations, opinions of scholars and the book of scientific interpretation. This study concludes that Scientific Interpretation is a part of the discourse on Al-Qur'an studies and interpretations whose existence cannot be avoided. There are differences of opinion among scholars regarding Scientific Interpretation, some accept and reject the presence of this interpretation. The presence of Scientific Interpretation adds to the scientific treasures of Qur'anic interpretation, especially in developing the principle of harmony between the Qur'an and science. One product that is an example of constructive and solutive ideas from Tafsir Ilmi is the birth of the book Tafsir Al-Kasyaf in the classical era and the Interpretation of the Ministry of Religion of the Republic of Indonesia in the modern-contemporary era. The weakness of this study is that it only explains topics related to Scientific Interpretation without explaining specifically the aspects of the text of the commentary product. Then, this study also recommends that we can study more deeply about the epistemology of Scientific Interpretation.